Perceptions of UIN Syahada Padangsidimpuan Students as Prospective Human Resources on the Implementation of Green Human Resource Management in Promoting a Green Economy in Islamic Institutions - Indah Permatasari Siregar; Asvika Rani Hutabarat; Nabilla Mei Saskia Putri Tanjung (Priviet Social Sciences Journal, 2026)
Islamic institutions play an important role in establishing a balance between economic growth and environmental preservation in accordance with Islamic principles. This study aims to determine the perceptions of students at UIN Syahada Padangsidimpuan as future human resources regarding the implementation of Green Human Resource Management (GHRM) in promoting a green economy in Islamic institutions. GHRM is seen as a human resource management strategy oriented towards sustainability and Islamic values. This study uses a descriptive qualitative method with data collection techniques conducted through an open questionnaire distributed to 59 students. The data were analyzed through the stages of reduction, presentation, and conclusion drawing. The results show that students have a positive perception of the application of GHRM as a form of moral and spiritual responsibility in protecting the environment. Islamic values such as trustworthiness, cleanliness, and responsibility as khalifah fil ardh are considered relevant in supporting green management practices. However, the implementation of GHRM in Islamic institutions still faces challenges in the form of limited policies and environmental awareness, but has great potential to be developed as a basis for strengthening a sustainable green economy.